How Free is a Fall That Occurs in Real World? - Sharma, Om; Sharma, Dipti (European Journal of Applied Sciences, 2021)
Observing a rain fall or falling leaves or tossing pizza dough in air, can give some thought of free fall. But how free are they? These types of questions can come to anyone’s mind when you see something falling in air to the ground. What is a free fall and how is different than not being a free fall? In my present research, I studied and tested concepts of free fall using various types of objects those are different in shape, size, weight, and volume. I tested them for free fall by dropping them from same height to find out how accurately they follow free fall conditions or if they do not follow free fall theory then what are the causes. Is there any experimental error that is causing a fall not to be a free fall, or it is natural or something else? I also tested how weight and height can affect free fall of objects. After experiments, it came out that objects those are very light in weight or very large in volume or have ability to hold air in it due to their shape show deviation from free fall concepts and counted as non-free fall objects.